Brain development during the lifespan of cynomolgus monkeys - Zhiqiang Tan; Binbin Nie; Huanhua Wu; Bang Li; Jingjie Shang; Tianhao Zhang; Zeyu Xiao; Chenchen Dong; Chunyuan Zeng; Biao Wu; Lu Hou; Bin Guo; et al. (NeuroImage)
The cynomolgus monkey has emerged as a predominant nonhuman primate model in neuroscience research. A comprehensive grasp of the growth and development patterns in the cynomolgus monkey brain is crucial for the judicious utilization of this species in neuroscience investigations. This project involved the collection of brain [18F]FDG PET-MRI data from 228 healthy cynomolgus monkeys spanning the age range of 0.5–29.5 years to construct an age-specific multimodal image brain template toolset tailored to cynomolgus monkeys. Their brain volume and glucose metabolism were quantitatively analyzed by utilizing an individualized spatial segmentation algorithm. Our findings encapsulated the growth and development trends, sex differences, and asymmetrical variations in brain volume and glucose metabolism in cynomolgus monkeys, and analyzed the correlation between the brain volume and glucose metabolism. This endeavor enhances our capacity to leverage the cynomolgus monkey model in neuroscience research by providing a valuable resource for researchers. The age-specific brain template toolset and associated data offer a robust foundation for future investigations, facilitating a nuanced understanding of brain development in this primate species and, consequently, informing and advancing neuroscience research employing cynomolgus monkeys.